Systematic Review: The Impact Of Pandemic Post-Covid-19 On The Mental Health Of The Elderly - Yulia Ayriza; Muhammad Zambri (Publisher Cv. Inara, 2023)
This study aims to investigate how MSMEs in Cilacap capacity to compete and perfome well in the marketing arena are The elderly are those who spend a lot of time at home to gather with their families and grandchildren, which is normal. This systematic review aims to look at the impact of the COVID-19 pandemic on the post-pandemic mental health of the elderly. based on research journal articles published from January 2022 to April 2022 on the elderly. Five research articles were obtained from three international publishers. The five journals were tested for due diligence using six PRISMA (Preferred Reporting Items for Systematic Review and Meta-analyses) assessment protocols which included abstracts and titles, introduction and objectives, methods and data, sample selection strategy, data analysis, and research findings. The results obtained based on a systematic study conducted in depth regarding the impact of Covid-19 on the health of the elderly are; (1) Psychological disorders, namely: anxiety, stress, overdose, and trauma. (2) Disorders of happiness, namely quality of life, perceptions of health and well-being (3) and Physical Disorders, namely functional disorders, dyspenia, and cognitive disorders. This finding represents the impact that the elderly have felt during the 4 months of the pandemic in 2022, even though it has been more than two years of the COVID-19 pandemic, the elderly are still feeling the negative impact of the pandemic. The third finding of the impact of the pandemic on the elderly can be used as reference material and a source of reference for in-depth research by linking variables that can increase positive emotions in individuals.